FOOD PATTERNS IN THE BRONZE-IRON AGE ARCHAEOLOGICAL SITE LERNAKERT IN ARMENIA: RESULTS OF ARCHEOZOOLOGICAL RESEARCH - Зарикян, Нушик; Мкртычан, Левон; Варданян, Беник (History, Archeology and Ethnography of the Caucasus, 2024)
In 2019-2021, excavations at the Late Bronze Age – Early Iron Age archaeological site of Lernakert on the northwestern slopes of Mount Aragats yielded a significant quantity of faunal remains. The archaeological complex comprises two cyclopean fortresses (Veri Berd and Vari Berd), tombs, and settlements. Archaeozoological analyses were conducted to identify dietary and food technology components in this region. The diversity of animal remains reveals diverse meat sources from both hunting and herding practices, highlighting the dynamic nature of food patterns over time. Reflecting a long history of animal exploitation influenced by social, cultural, and environmental factors, this study aims to characterize the unique features of animal-derived food resources at this settlement, outlining the economy and inhabitants’ activities during the late Bronze Age to Early Iron Age. Therefore, our paper states, that the main difference between the Bronze Age and the Iron Age was the agricultural and economic progress to a better standard of living, and the differentiated food patterns of Lernakert have been the tools for adapting to the local geography and unfavorable environment. While acknowledging the potential role of social interaction in shaping food patterns, further investigation is needed. The methodology employs osteological analysis of animal remains excavated from Lernakert’s Veri Berd, Vari Berd, and settlement areas. The results reveal the diverse husbandry practices and food types of this period, highlighting the evolution of livestock management between the Bronze and Iron Ages.
Keywords: Animal remains; dietary; Lernakert; meat consumption; North-west Armenia communities.